Five Years after the Reform: The Financial Sustainability of the Pension System of Georgia and EU27 Countries - Jgerenaia, Emzar; Ghaniashvili, Maka (International Journal of Economics and Financial Issues, 2025)
The aging population, caused by longer life expectancy and low birth rates, has led to a crisis in the public pension system in many countries. Changes are necessary to ensure the system’s sustainability. The primary goal of pension system reforms in many countries is to reduce fiscal pressure in macroeconomic terms and, on a microscale, guarantee decent old age and adequate income for retirees. The paper aims to determine pension systems’ sustainability in Georgia and EU countries based on the Open Method of Coordination (OMC) indicators. OMC evaluates pension systems in terms of three main objectives: adequacy, sustainability, and modernization of pensions. Our methodology is based on multivariate statistical analysis and employs synthetic indicators, such as pension expenditure, employment rate of people aged 55–64, and duration of working life for 2010, 2015, 2018, and 2023 sustainability objectives. The results of our study show an adverse change in pension system sustainability indicators from 2010 to 2023 in most European countries, including Georgia. The sustainability index of Georgia’s pension system has deteriorated since 2010.